The daily association between positive affect and psychotic experiences in individuals along the early stages of the psychosis continuum - van der Tuin, Sara; Staines, Lorna; Morosan, Larisa; Raposo de Almeida, Esdras; van den Berg, David; Booij, Sanne H.; Oldehinkel, Albertine J.; Wigman, Johanna T. W. (Frontiers in Psychiatry, 2024)
Introduction Psychosis often develops gradually along a continuum of severity. Little is known about the role of protective factors such as positive affect (PA) in the development of psychotic experiences (PEs). This study investigated i) the temporal (between-day) and contemporaneous (within-day) daily associations between PA and PEs in individuals at different early clinical stages for psychosis and ii) whether these associations differed per clinical stage. Methods Daily diary data for 90 days came from 96 individuals at risk for psychosis, distributed over four subgroups defined according to the clinical staging model (stages 0–1b). We constructed multilevel models with PA as a predictor of PEs and vice versa. We investigated within- and between-person temporal and contemporaneous associations and tested whether these associations differed among early stages with multilevel moderation analyses. Results We found no within-person temporal effects between PA and PEs in either direction. Contemporaneously, current-day PA predicted current-day PEs (B = −0.14, p < 0.001) and vice versa (B = −0.61, p < 0.001). Between persons, more 90-day PA predicted fewer PEs in the temporal model (B = −0.14, p = 0.03). In addition, more 90-day PEs predicted PA in the temporal (B = −0.26, p < 0.001) and contemporaneous (B = −0.36, p < 0.001) models. The contemporaneous association between PA and PEs was stronger in individuals at ultra-high risk (UHR) for psychosis than in earlier stages. Discussion Our study supported a significant within-day, bidirectional relationship between PA and PEs. This suggests that a focus on PA and methods to improve PA may be an important addition to early intervention practices, particularly in those at UHR for psychosis.